MEDICAL EDUCATION AND SOCIAL ENVIRONMENT - Rasool, Ahsan; Qayum, Iftikhar; Ahmad, Ashfaq; Farooq, Umer; Shah, Awais Ali; Waqas, Muhammad; Rasool, Maleeha; Hameed, Sania; Kanwal, Rana; Azmat, Muneeba; Marwat, Saleem; Afridi, Faheem (Journal of Ayub Medical College Abbottabad, 2014)
Background: A positive learning environment and quality of course content have an imperative role in academic achievement of students. This study aims to assess students' point of view about the quality of education and social environment of a public sector medical college in Pakistan. Relative scarcity of data from students' perspective merited this study. Methods: A cross-sectional survey was undertaken at Ayub Medical College, Abbottabad, Pakistan, including 300 medical students from all five years of the MBBS course. Systematic random sampling was used with a kth interval of 4 for each class. Self-administered questionnaire was used and contained items related to academics, learning environment, learning resources, teaching methodologies and student-friendly activities. The data were analysed using SPSS-16. Results: There were 265 respondents (88.3%) to the questionnaire with males accounting for 58.9% (n=156). In general students showed satisfaction with quality of content being taught; however there was discontent towards various academic and non- academic facilities provided to the students. Only 44.10% and 31.50% students reported provision of academic related facilities and interactive sessions as up to mark respectively; 83% students reported that undergraduate medical research was in need of improvement; 55.5% and 60.2% reported that facilities in hostel and recreational facilities needed improvement respectively; and 52.8% students stated presence of a healthy, student friendly, encouraging environment was not up to mark. Conclusion: Although course content and teaching methodologies are generally satisfactory, a healthy, student friendly, encouraging environment is yet to be created to help students foster their abilities completely. Keywords: Medical education, Social environment, Academics, Learning resources